2016
DOI: 10.1111/medu.12942
|View full text |Cite
|
Sign up to set email alerts
|

Do OSCE progress test scores predict performance in a national high-stakes examination?

Abstract: CONTEXT Progress tests, in which learners are repeatedly assessed on equivalent content at different times in their training and provided with feedback, would seem to lend themselves well to a competency-based framework, which requires more frequent formative assessments. The objective structured clinical examination (OSCE) progress test is a relatively new form of assessment that is used to assess the progression of clinical skills. The purpose of this study was to establish further evidence for the use of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…As found in this study, we observed that in the area of medicine, the PT is considered to be a "training" so that students, after completing their undergraduate course, were better prepared to take the medical qualification tests. (18) The effective development of these questions, however, is so laborious that a software was developed (19) able to measure cognitive knowledge in tests with multiple choice questions.…”
Section: Discussionmentioning
confidence: 99%
“…As found in this study, we observed that in the area of medicine, the PT is considered to be a "training" so that students, after completing their undergraduate course, were better prepared to take the medical qualification tests. (18) The effective development of these questions, however, is so laborious that a software was developed (19) able to measure cognitive knowledge in tests with multiple choice questions.…”
Section: Discussionmentioning
confidence: 99%
“…Progress tests appear to have tangible benefits beyond those of simply measuring progress. The use of written progress tests has been linked to improved performance in a national licensure examination, whereas objective structured clinical examinations (OSCEs) used as progress tests have been shown to be useful in identifying residents at risk of subsequently failing a high‐stakes national examination of clinical skills …”
Section: The Role Of Progress Testingmentioning
confidence: 99%
“…The use of written progress tests has been linked to improved performance in a national licensure examination, 20 whereas objective structured clinical examinations (OSCEs) used as progress tests have been shown to be useful in identifying residents at risk of subsequently failing a high-stakes national examination of clinical skills. 21 Perhaps more importantly, however, the comprehensiveness of progress tests, coupled with the relatively low-stakes nature of the format, may serve to mitigate some of the subversive effects of AOL on learning. For example, because there is no functional limit on the content being assessed, strategies such as targeted studying, memorisation, cramming and teaching to the test are unlikely to be particularly useful.…”
Section: The Role Of Progress Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of publications has utilized electronic OSCE scoring systems for exam practice and for prospective research 19 ,21,22 . Cross-institutional comparison of student achievements in a progress test have been published for benchmarking purposes [23][24][25][26] . Studies evaluating the context between education and assessments largely reported comparisons between different methods of teaching 27,28 .…”
Section: Introductionmentioning
confidence: 99%